How Transportation Restriction Shapes the Relationship Between Ambient Nitrogen Dioxide and COVID-19 Transmissibility: An Exploratory Analysis - Han, Lefei; Zhao, Shi; Cao, Peihua; Chong, Marc K. C.; Wang, Jingxuan; He, Daihai; Deng, Xiaobei; Ran, Jinjun (Frontiers in Public Health, 2021)
Background: Several recent studies reported a positive (statistical) association between ambient nitrogen dioxide (NO2) and COVID-19 transmissibility. However, considering the intensive transportation restriction due to the implementation of lockdown measures would lead to declines in both ambient NO2 concentration and COVID-19 spread, the crude or insufficiently adjusted association between NO2 and COVID-19 transmissibility might be confounded. This study aimed to investigate whether transportation restriction confounded, mediated, or modified the association between ambient NO2 and COVID-19 transmissibility. Methods: The time-varying reproduction number (Rt) was calculated to quantify the instantaneous COVID-19 transmissibility among 31 Chinese cities from January 1, 2020 to February 29, 2020. For each city, we evaluated the relationships among ambient NO2, transportation restriction, and COVID-19 transmission under three scenarios, including simple linear regression, mediation analysis and adjusting transportation restriction as a confounder. The statistical significance (p-value < 0.05) of three scenarios in 31 cities was summarized by percentages. Results: We repeated the crude correlational analysis, and also found the significantly positive association between NO2 and COVID-19 transmissibility. We found that little evidence supported NO2 served as a mediator between transportation restriction and COVID-19 transmissibility. The association between NO2 and COVID-19 transmissibility appears less likely after adjusting the effects of transportation restriction. Conclusions: Our findings suggest the crude association between NO2 and COVID-19 transmissibility is likely confounded by the transportation restriction in the early COVID-19 outbreak. After adjusting the confounders, the association between NO2 and COVID-19 transmissibility appears unlikely. Further studies are warranted to validate the findings in other regions.